Strengthening Child-Friendly School Policy Implementation through Community Empowerment in Early Childhood Education Settings - Cici Hayati; Dessy Novianty; Ghaida Tsuraya; Karmila Sari; Maizanur Riski; Mely Nur Juliana; Metroyadi Metroyadi; Aeman Shemi Shamsuddin (Journal of Comunity Service in Early Childhood Education, 2025)
Background: The implementation of Child-Friendly School (SRA) policies in early childhood education remains a critical issue, particularly in ensuring safe, inclusive, and rights-based learning environments. Many institutions still face challenges in translating policy into practical classroom implementation. Aims: This community service program aims to strengthen the implementation of Child-Friendly School policies through capacity building and mentoring for teachers in early childhood education settings. Methods: This program employed a community development approach with an empowerment strategy, involving collaboration between lecturers and teachers. The implementation consisted of three stages: (1) awareness building through socialization and workshops on child-friendly school principles, (2) mentoring teachers in designing and implementing child-centered and inclusive learning practices, and (3) evaluation through observation and reflective discussions. Data were collected through observation, interviews, and documentation, and analyzed descriptively. Results: The results indicate an improvement in teachers’ understanding and application of child-friendly school principles, including the development of safe and inclusive learning environments, the use of non-discriminatory and child-centered approaches, and increased child participation in learning activities. In addition, stronger collaboration between teachers and parents was observed in supporting child-friendly practices. However, several challenges remain, such as limited learning facilities and teacher workload constraints. Conclusion: The implementation of child-friendly school policies through a community empowerment approach effectively enhances teachers’ capacity and supports the creation of inclusive and child-centered learning environments. This program offers a practical and adaptable model for strengthening policy implementation in early childhood education.